288 Forage mineral and nutrient element concentrations on sheep winter range. (30th November 2020) - Julian, Alexis; Scasta, Derek; Stam, Barton; Sebade, Brian; Page, Chad M; Springer, Brady; Renner, Wilson; Cunningham, Hannah; Stewart, Whit C
Abstract: Supplementation strategies and nutritional management of ewes during critical production periods of breeding and gestation is an important consideration, particularly when ewes are on winter range. Clinical and subclinical trace mineral deficiencies at these times limit ewe productivity in these extensive environments. The objectives of this study were to (1) quantify mineral element concentrations of common forages on winter range, and (2) evaluate producer supplementation strategies using a survey. We hypothesized that mineral element concentrations in winter forages were inadequate to meet ewe requirements during critical production stages and shrub species would contain higher levels of macro- and micro-mineral element concentrations than grass species. Forage samples were collected from 25 ranches across Wyoming winter range and were compiled by species and analyzed for nutrient and mineral element composition; however, data presented herein represents the first year of data collection (12 of 25 ranches). Nutrient and mineral element concentration results indicated an effect in CP, Ca, P, K, Mg, S, Na, Zn, Cu, Se, Mn, and Mo concentrations between grass and shrub species (P < 0.05). Specifically, Mg and Mo concentrations were higher in grasses while the other mineral element concentrations were higher in shrubs. No effect was observed for Fe and Co concentrations between grass and shrub species (P = 0.37 and P = 0.29). Survey results revealed that 80% of ranches had more than 1000 sheep, and 47% of respondents utilized winter range for 131 to 170 day periods throughout production year. While on winter range the majority of producers (47%) supplement with a protein source. Additionally, 58% do not supplement white salt, while 47% supplement a complete trace mineral mix.